SERUM OESTRADIOL 17β CONCENTRATION OF HORMONE INDUCED POST-PARTUM ANOESTRUS SOWS (Indian Journal of Animal Production and Management, 2014)
Indigenous post partum anestrous sows of Assam could be effectively brought into ovulatory oestrus by administering combination of PMSG and HCG and áGNRH with satisfactory conception rate. This study, constituting 18 numbers of indigenous post partum anoestrus sows, were divided into three groups, consisting of six animals in each group. Group A was treated with a initial dose of 0.017 (4 ml) of GnRH analogue (Receptal ) intramuscularly followed by 0.78 mg (4ml) of PGF2α analogue (Illirin) on 14 day of initial treatment. After 48 hours of PGF2α analogue (Illirin) injection 0.008 mg (2ml) of Receptal was given intramuscularly. Animals under group B were treated with single dose of 200 IU (1ml) of PMSG (Folligon) intramuscularly combined with 150 IU (0.5ml) of HCG (Chorulon). Whereas, the animal of group C (control group) were administered with single intramuscular injection of sterile normal saline. All animals were observed for the occurrence of oestrus. Blood collection was done prior to and after treatment on different days in the 3 groups of anoestrous of sows and serum concentration of oestradiol 17β were estimated by RIA (radio immunoassay. Hundred percent oestrus could be achieved in group A and B anoestrous sows than control group (C). Serum oestradiol 17β differed significantly (P
Keywords: Anestrus; Indigenous Sows; Hormone